Enhancement of Biodegradation of Chlorpyrifos and Carbaryl of Gill, Muscle, Liver Tissues of Cyprinus Carpio - Muniyasamy, Aurumugam; Prabakaran, Victor (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pesticides are powerful agents that kill non- target animals and unwanted insects in a particular area. Chlorpyrifos bioaccumulate leading to increased contamination in soil and water. This study was focused with much attention to curb the menace of the pollution. Biodegradation is the process by which microorganism such as Pseudomonas aeruginosa advocate for biodegradation which is consider to be a clean-up technology. In our study 30% of degradation was recorded. The fish Cyprinus carpio was used as an indicator animal and its gill, muscle, liver tissue was analyzed for pesticide residue accumulation where in the biochemical changes such as protein were depleted due to pesticide toxicity. Subsequently an increase protein content was noted in the biodegradation experimental sets. Other pesticides carbaryl the active ingredient of sevin which cause drastic effect on non-target animals was degraded by the enzymatic machinery of the Pseudomonas aeruginosa.